Posterior Segment Retained Intraocular Foreign Body: A Study from Western Nepal - Thapa, Bikram Bahadur; Singh, Sweta; Lamichhane, Gyanendra; Gurung, Shanti; Piya, Saurav (Nepalese Journal of Ophthalmology, 2021)
Introduction: Posterior segment retained Intraocular foreign body (IOFB) management is challenging. Facility of pars plana vitrectomy (PPV) and availability of well trained vitreo retina surgeons are the basic need to accomplish this work.  Encircling band provide permanent 360° support to close the anterior retinal break and prevent traction on the retina. The objective of this study is to analyse the clinical characteristics and predictors of the final visual outcome and survival of the globe in cases of retained IOFB in the posterior eye segment.Materials and methods: A hospital based retrospective observational study was conducted. All the patients of retained IOFB in the posterior segment presented from January 2016 to June 2019 were enrolled. Patients presented with visual acuity of NPL were excluded. Statistical analysis was performed using a variety of tests using SPSS version 21.  Results: Forty eyes of 40 patients were included. The mean age was 27.08±10.68 years (range 5-66). 95% of our patients were male. Most of them (52.5%) worked on the farm. 26(65%) of 40 eyes had Zone I injury. The median time spent before presentation was 13.5 day. Retinal detachment, vitreous hemorrhage, and endophthalmitis were present in 15, 23 and 5 eyes, respectively, before IOFB removal. The mean LogMAR visual acuity was improved significantly from 2.50±0.87 to 1.33± 1.01 (p=0.003). Poor presenting visual acuity, retinal detachment and large diameter of IOFB were found as the predictor of poor final visual acuity.Conclusion:  Pars plana vitrectomy by a vitreo retinal surgeon can give encouraging results in the cases of retained posterior segment IOFB. Poor presenting visual acuity, large diameter of IOFB and RD before IOFB removal are predictors of poor visual outcome.